Factors influencing the basic needs budget among the middle income earners in selected major cities in Malaysia - Rusli Latimaha; Zakaria Bahari; Nor Asmat Ismail (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper investigated the main factors influencing the basic needs budget in three major cities with a high cost of living in Malaysia. The analysis of variance tests result indicated that the Federal Territory of Kuala Lumpur, the state of Penang and Johor are places with high cost of living. The result also revealed that the middle income group are those who earn an income between RM2,992.50 to RM8,999 a month and the salaries of teachers were used as a proxy for the middle income groups. The Ordinary Least Squares (OLS) regression analysis indicated that there is a difference between the basic needs budget for single-adults and one-working parent families and furthermore, the basic needs budget in the cities of Kuala Lumpur, Johor Baharu and George Town is slightly different in each town. By and large, there is a difference in the basic needs budget between single-adults in Kuala Lumpur and Johor Bahru, and between two-working parent families among the three major cities. It is however interesting to note that there is no difference in the basic needs budgets among one-working parent families in these cities. The results also revealed that the total household income, family size, age of head of household, sex ratio, number of rooms, electrical appliances usage cost, broadband subscribers and number of privately owned cars all significantly influenced the basic needs budget regardless of which cities the respondents live.